Influence of Innovation and Work Environment on Performance with Work Discipline as Mediator - Suryana, Titik; Aprianto, Ronal; Fitria; Suyadi (Universitas Bumigora, 2025)
This study aims to analyze the influence of technological innovation and work environment on employee performance at Tugu Perfect Farmers Group (KTGA), Division 1 PNDA Djuanda Sawit Lestari, with work discipline as an intervening variable. Technological innovation is expected to enhance efficiency and productivity, while a conducive work environment fosters employee motivation and job satisfaction. This research employs a quantitative approach, utilizing path analysis with SmartPLS 3, to examine the relationships between variables based on data collected from 63 employees through a structured questionnaire. The results indicate that technological innovation has a significant and positive impact on employee performance, both directly and indirectly through improved work discipline. Similarly, the work environment has a positive impact on performance, with work discipline serving as a significant mediator. The novelty of this study lies in its integrated examination of work discipline as a mediating variable in the agricultural and plantation sector. This area has remained underexplored in previous research. The findings underscore the importance of integrating technological advancements with a sup- portive work environment and strong work discipline to enhance performance outcomes. Practically, this study provides actionable insights for human resource management, particularly for plantation-based companies, to develop strategic interventions that focus on employee adaptability, discipline, and moti- vation. It contributes to the literature by emphasizing the role of organizational culture and behavioral factors in enhancing employee performance through digital transformation and workplace improvement.